Bias Within: Examining the Role of Cultural Competence Perceptions in Mammography Adherence. (20th March 2015) - Hall, Marla B.; Carter-Francique, Akilah R.; Lloyd, Stacy M.; Eden, Tiffany M.; Zuniga, Angie V.; Guidry, Jeffrey J.; Jones, Lovell A.
Breast cancer mortality has affected African American women at a disproportionate rate. The purpose of this research was to assess how health professionals' cultural competence contributes to African American women's barriers to and receipt of mammograms. Sixty-one African American women residing in Harris County, Texas, shared their views within a series of focus groups. Theoretical propositions from the PEN-3 model were used to understand mammography adherence at the interpersonal level. Participants noted various perceived factors associated with mammography incompliance. Lack of professionalism of clinicians and clerical staff contributed to a decrease in health care services utilization. In addition, cultural insensitivity and discriminatory behavior enabled an attitude of medical mistrust. Improving patient–provider communication, through culturally appropriate centered educational efforts, is a beneficial strategy for breast health programs among underserved populations.